Chicken soup for little souls. The never-forgotten doll - McCourt, Lisa.; Young, Mary O'Keefe; Canfield, Jack, 1944- (Deerfield Beach, Fla. : Health Communications, 1997)
Ellie's love for Miss Maggie, her baby-sitter, helps her find a way to give Miss Maggie the best birthday present ever.
"Inspired by the ... bestseller Chicken soup for the soul by Jack Canfield and Mark Victor Hansen"--Cover.
"Story adapted from A doll for great-grandmother by Jacqueline Hickey."
School Library Journal
4.2
K-3
Keywords: Babysitters -- Fiction; Friendship -- Fiction; Dolls -- Fiction; Gifts -- Fiction; Birthdays -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Dolls -- Fiction; Gifts -- Fiction; Birthdays -- Fiction